The Language Question in Şalom (1947–1983): Linguistic Ideologies among the Sephardim of Turkey - Corral, Adrián Martínez (European journal of jewish studies, 2021)
Abstract Since the beginning of the Judezmo press in the second half of the nineteenth century, “the language question” has been a recurrent topic of debate. Throughout the pages of the many newspapers in Judeo-Spanish, several linguistic ideologies were exposed, often causing heated controversies. The aim of this article is to analyze the views, assumptions and conceptions regarding the many languages employed by the Sephardim of Turkey during the second half of the twentieth century. Şalom , a Judezmo newspaper published in Istanbul from 1947 onwards, will be the source informing this analysis. Finally, it will be observed whether such linguistic ideologies had an impact on the domains of use of the languages employed by Turkish Jewry and helped to conform the current linguistic landscape of the community.